Exogenous Flupirtine as Potential Treatment for CLN3 Disease - Katia Maalouf; Joelle Makoukji; Sara Saab; Nadine J. Makhoul; Angelica V. Carmona; Nihar Kinarivala; Noël Ghanem; Paul C. Trippier; Rose-Mary Boustany (Cells, 2020)
CLN3 disease is a fatal neurodegenerative disorder affecting children. Hallmarks include brain atrophy, accelerated neuronal apoptosis, and ceramide elevation. Treatment regimens are supportive, highlighting the importance of novel, disease-modifying drugs. Flupirtine and its new allyl carbamate derivative (compound 6) confer neuroprotective effects in CLN3-deficient cells. This study lays the groundwork for investigating beneficial effects in Cln3Δex7/8 mice. WT/Cln3Δex7/8 mice received flupirtine/compound 6/vehicle for 14 weeks. Short-term effect of flupirtine or compound 6 was tested using a battery of behavioral testing. For flupirtine, gene expression profiles, astrogliosis, and neuronal cell counts were determined. Flupirtine improved neurobehavioral parameters in open field, pole climbing, and Morris water maze tests in Cln3Δex7/8 mice. Several anti-apoptotic markers and ceramide synthesis/degradation enzymes expression was dysregulated in Cln3Δex7/8 mice. Flupirtine reduced astrogliosis in hippocampus and motor cortex of male and female Cln3Δex7/8 mice. Flupirtine increased neuronal cell counts in male mice. The newly synthesized compound 6 showed promising results in open field and pole climbing. In conclusion, flupirtine improved behavioral, neuropathological and biochemical parameters in Cln3Δex7/8 mice, paving the way for potential therapies for CLN3 disease.